Penguatan Kelompok Wanita Tani dalam Mendukung Ketahanan Pangan Rumah Tangga di Kabupaten Jeneponto - Rasdiana Mudatsir; Sumarni (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
Strengthening Women Farmer's Groups requires the involvement of extension workers through programs and activities that impact the food security of farmer households. Extension workers' involvement is expected to positively impact the strengthening of Women Farmers Groups (KWT) in Tarowang District, Jeneponto Regency, South Sulawesi. The study's objectives were (1) to analyze the role of KWT in household food security and (2) to describe the KWT strengthening model used in supporting household food security. The instrument used in the study was an in-depth interview. Data were processed using tabulation techniques and analyzed using descriptive methods. The results of the study showed (1) the role of KWT in supporting household food security is increasing food production, increasing human resources, increasing agricultural product marketing, family food diversity, farmer household income, and increasing women's empowerment; (2) the institutional strengthening model of KWT in supporting household food security is a model of institutional support and increasing the capacity and skills of KWT members.